Conceptual design of production of eco-friendly polyoxymethylene dimethyl ethers catalyzed by acid functionalized ionic liquids. (12th October 2019) - Wang, Dan; Zhu, Gangli; Li, Zhen; Xue, Machen; Xia, Chungu
Graphical abstract: Highlights: DMM 3-n production is feasible with acid functionalized ionic liquids in large scale. Composition controlled process without de-heavy column to avoid units blockage. Activity coefficients by solid-liquid equilibrium data agree well with VLE data. Both energy consumption and fixed capital investment can be saved by the design. Cold-flow properties and flash points of diesel blends measured for specifications. Abstract: As the clean fuel additives, polyoxymethylene dimethyl ethers (DMM n ) could significantly reduce carbonaceous particulate matters and volatile organic pollutants in the exhaust gas. Large scale production in a green route would be crucial if the DMM n tailored diesel was applied to the abatement of widespread PM air pollution. In the production, heavy components usually should be separated, recycled, decomposed and re-reacted to gain the aimed products, which would significantly increase complexity and energy consumption of the process. And fatally, it also might cause blockage of units and pipelines. In this work, to prevent blockage, the facile and robust process producing DMM n was conceptually designed basing on physicochemical properties researches. The process exempting from recycle of heavy components and de-heavy column was proposed according to cold-flow properties. Both energy consumption and fixed capital investment can be saved. The reaction kinetic model, which was described in the form of power law functions, showed good consistency for both propagation and depolymerization reactions. Flash points of diesel blends were also measured for determining specification of light components. This work shows it is feasible that DMM n can be produced from dimethoxy methane and trioxane in the presence of acid functionalized ionic liquids in large scale.